Malaysia seaport development: A study on new entrants and supplier based on Michael E. Porter competitiveness forces model at Westport, Port Klang Malaysia - B., Noorlee; J., Jagan; M.S., Roszita; A.H., Saharuddin (2010)
The development and growth in port and shipping industries will be effected to the economy of Malaysia.The research aims to identify the main efficient strategy from suppliers to develop the main supplier, effective strategy to handle the threats from new entrants and to measure the important of the most cost effective supplier.The research is consists only on two parts of Michael E. Porter Competitiveness Forces Model which are new entrants and supplier.The research will be conducted by using a few methods with the first method are by using secondary data from books, journals and from internet sources. Second method is by distributing the questionnaire from respondents, then will be analyze by SPSS system.These researches will be expected to gain the efficient and effective strategy with some recommendation to make more competitiveness at Westport, Port Klang Malaysia.